THE OPTIMIZATION EFFECTIVE GREEN TO REDUCE THE QUEUE IN INTERSECTION SEKARSARI MOJOKERTO CITY - Soewartono, Edhi (EXTRAPOLASI, 2013)
One of the few intersections in Mojokerto Town conflict that has four arms crossing congestion isSekarsari such as Jl. Gajah Mada, Jl. Empunala, Jl. Resident Pamuji most frequent congestion at peak hourswhere heavy traffic flows and vehicle frequency is high enough, to know how much effective green optimumis needed to resolve conflicts, determining the most effective phase, aims and objectives of this study is toprovide an evaluation in order to improve the level of service at the intersection of the four arms Sekarsari,and to provide an alternative solution of the problem of traffic jams that occur at the intersection. Byperforming calculations and analysis of existing conditions, at a time get Allred, congestion, trafficflow.,intersection, traffic light signals. At each approach is only 2 seconds and degree of saturation on theapproach A = 0.95, B = 0:52 approach, approach C = 0.76, D = 0.76 approach. These results do not fit likethe recommended Dirjen Bina Marga, the degree of saturation is less than 0.85 for signalized intersections.To do some remedial alternatives for traffic signal. Researchers try 8 alternative traffic signal. The alternativecalculation to get the result that is considered the most appropriate and optimal traffic signal setting 3 phase,approach B, left and widening approach D direct turn A (originally 8,5 m to 10 m) and approach C (originally8.5 m to 8.75 m ). With this alternative, get results in 95 seconds cycle time, Allred Time for A = 5detikapproach, approach deik B = 7, C = 5 second approach, approach D = 2 seconds, the degree of saturationapproach to approach A = B = C , approach D = 0.80.Key word:effective green, intersection